Role of Prohibitins in Aging and Therapeutic Potential Against Age-Related Diseases - Belser, Misa; Walker, David W. (Frontiers in Genetics, 2021)
A decline in mitochondrial function has long been associated with age-related health decline. Several lines of evidence suggest that interventions that stimulate mitochondrial autophagy (mitophagy) can slow aging and prolong healthy lifespan. Prohibitins (PHB1 and PHB2) assemble at the mitochondrial inner membrane and are critical for mitochondrial homeostasis. In addition, prohibitins (PHBs) have diverse roles in cell and organismal biology. Here, we will discuss the role of PHBs in mitophagy, oxidative phosphorylation, cellular senescence, and apoptosis. We will also discuss the role of PHBs in modulating lifespan. In addition, we will review the links between PHBs and diseases of aging. Finally, we will discuss the emerging concept that PHBs may represent an attractive therapeutic target to counteract aging and age-onset disease.